Short-interference RNAs: becoming medicines - Martínez, Tamara; Jiménez, Ana Isabel; Pañeda, Covadonga (Technische Universität Dortmund, 2015)
RNA interference is a cellular mechanism by which small molecules of double stranded RNA modulate gene expression acting on the concentration and/or availability of a given messenger RNA. Almost 10 years after Fire and Mello received the Nobel Prize for the discovery of this mechanism in flat worms, RNA interference is on the edge of becoming a new class of therapeutics. With various phase III studies underway, the following years will determine whether RNAi-therapeutics can rise up to the challenge and become mainstream medicines. The present review gives a thorough overview of the current status of this technology focusing on the path to the clinic of this new class of compounds.
EXCLI Journal;Vol. 14, 2015
Keywords: siRNA; RNAi; oligonucleotides; therapeutics; 610